2013
DOI: 10.1155/2013/139239
|View full text |Cite
|
Sign up to set email alerts
|

Adipose Tissue in Obesity-Related Inflammation and Insulin Resistance: Cells, Cytokines, and Chemokines

Abstract: Adipose tissue is a complex organ that comprises a wide range of cell types with diverse energy storage, metabolic regulation, and neuroendocrine and immune functions. Because it contains various immune cells, either adaptive (B and T lymphocytes; such as regulatory T cells) or innate (mostly macrophages and, more recently identified, myeloid-derived suppressor cells), the adipose tissue is now considered as a bona fide immune organ, at the cross-road between metabolism and immunity. Adipose tissue disorders, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
742
3
27

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 883 publications
(831 citation statements)
references
References 119 publications
23
742
3
27
Order By: Relevance
“…2. MR antagonism with eplerenone or spironolactone improves metabolic disorders and insulin resistance in obese and diabetic mice (9,18,19,33). 3.…”
Section: Discussionmentioning
confidence: 99%
“…2. MR antagonism with eplerenone or spironolactone improves metabolic disorders and insulin resistance in obese and diabetic mice (9,18,19,33). 3.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduction of IL‐1β, IL‐6, and TNF‐α has been implicated in several inflammatory diseases (Makki, Froguel, & Wolowczuk, 2013). IL‐1β and IL‐6 are important inflammatory cytokines secreted by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines, especially TNF‐α, highly induce an insulin resistance in adipocytes in which the insulin signaling is interrupted resulting in an impaired glucose uptake (Makki et al., 2013; Nieto‐Vazquez et al., 2008; Rotter, Nagaev, & Smith, 2003). Although ABE had no effect on TNF‐α production in the LPS‐treated macrophages, we found that a low dose of ABE (50 μg/ml) could inhibit TNF‐α‐induced insulin resistance in adipocyte as shown by the increased glucose uptake.…”
Section: Discussionmentioning
confidence: 99%
“…В нашем исследова-нии связь с выраженностью ожирения отмечена для M-CSF и IL-6. Корреляции IL-6 с окружностью талии, уровнем мочевой кислоты и триглицеридов согласуются с данными о роли этого цитокина в формировании инсули-норезистентности [27]. Известно, что адипоциты челове-ка секретируют IL-6 [28], M-CSF [29], MIF [30] и другие цитокины.…”
Section: Discussionunclassified